Gastrointestinal manifestations of Fasciolopsis buski associated polyparasitism in patients of an endemic area: a hospital based study - Ranjan, Shilpi; Saurabh, Kumar; Prasad, Rajeev Ranjan (International Journal Of Community Medicine And Public Health, 2017)
Background: The objective of the study was to describe the gastrointestinal manifestations of Fasciolopsis buski associated polyparasitism. Methods: A retrospective study in the form of chart review of twenty patients was done who passed either adult F. buski or ova per stool and their stool samples were also positive for other intestinal parasites. This study was done in a tertiary care centre of north Bihar during the time period of January 2016 to December 2016. Gastrointestinal manifestations of the patients were evaluated and treatment outcome was seen. Results: School age children were the most affected population. Diarrhoea either acute or persistent was the most common presentation. Some and severe dehydration was present in 50% cases. Pain abdomen (60%) was the common finding in children whereas adults having abdominal distension (40%) as a major complain. Anaemia was present in almost all cases. 30% cases even required blood transfusion. H. nana was the most common associated parasite followed by Ascaris. One patient had evidence of five different parasites in his stool sample. Patients were treated with Praziquantal, Albendazole and Metronidazole with complete recovery. Conclusions: F. buski associated with polyparasitism presents with a more severe form of disease than Fasciolopsiasis itself. Aggressive treatment is required.